Thyrotoxicosis Associated with a Hypopharyngeal Toxic Nodular Thyroid. (2nd November 2017) - Imran, S. Ali; Hinchey, Adam; Hart, Rob; Bullock, Martin; Ross, Andrew; Burrell, Steven
Abstract : Ectopic thyroid is a rare developmental anomaly which may be either asymptomatic or present with thyroid dysfunction as well as pressure symptoms. Here we present a novel case of thyrotoxicosis associated with a hypopharyngeal multinodular thyroid in a female. Removal of the ectopic thyroid led to normalization of the thyroid status.